Characteristics of an Impaired PDT Response. (24th February 2021) - Kessel, David; Cho, Won Jin; Rakowski, Joseph; Kim, Harold E.; Kim, Hyeong‐Reh C.
Abstract: A concurrent human papilloma virus (HPV) infection potentiates the efficacy of ionizing radiation for treatment of head and neck cancer by promoting apoptosis. Studies in cell culture indicated an opposite effect for photodynamic therapy (PDT) when this leads to mitochondrial and ER photodamage. The explanation for this difference in PDT efficacy remains to be established. While apoptosis was impaired in HPV(‐) cells, such cells can be killed via photodamage directed at the ER: this leads to a nonapoptotic death pathway termed paraptosis. No differences in photosensitizer uptake or reactive oxygen species (ROS) production were observed in HPV(+) vs. HPV(‐) tumors. We now provide evidence that death pathways initiated by ER/mitochondrial photodamage leading to either paraptosis or apoptosis are impaired in an HPV(+) head and neck cell line. These results illustrate the complex determinants of PDT efficacy, a topic that has yet to be fully explored. Abstract : This image demonstrates the ability of photodynamic therapy (PDT) directed at ER/mitochondria to eradicate a head & neck cancer cell line (WSU12) from a patient with a human papilloma virus infection. These cells were relatively unresponsive to ionizing radiation, typical of HPV(+) tumors. In contrast, cells from an HPV(‐) patient (UP154) were responsive to ionizing radiation but not to PDT.